Contact models for the representation of joint clearances in multibody mechanical systems - Flores, Paulo (2004)
Two general methodologies for dynamic modeling of joint clearances in multibody mechanical systems are presented throughout this work. In the first approach the elements that compose the joint clearance are considered as colliding bodies and contact-impact forces control the behavior of the joint. A continuous contact force model provides these intra-joint contact-impact forces. From the system configuration, a geometric condition defines whether or not the joint elements are in contact. In this model the clearance plays a key role in the joint performance. As far as the second model is concerned, it takes advantage of the analytical definition of the contacting surfaces within the joint clearance. The problem is regularized avoiding the use of the clearance as the primary variable, leading to a contact force formally similar to the Hertz model. This force is specifically formulated in the context of an energy-momentum time integration. The two different methodologies presented in this work are compared with the help of numerical simulations of an elementary mechanical system in which one of the revolute joints has a specified clearance.